Tebal Kerabang dan Volume Telur Berbagai Jenis Ayam Kedu di Kelompok Ternak Makukuhan Mandiri Kecamatan Kedu Kabupaten Temanggung - Rangga Okta Saputra; Rosidi Rosidi; Sigit Mugiyono (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this study was to determine whether there are differences in shell thickness and egg volume in various Kedu chickens. Materials and methods. The research was conducted using the survey method and the method of determining the sample using the purposive random sampling method. The variables observed were shell thickness and egg volume. The research design used RAL (completely randomized design) with five different treatments and four replications. The data obtained were then tabulated, then analyzed using the General Linear Model (GLM). Results. The results showed that the average shell thickness of various types of Kedu Chickens was 0.405 ± 0.03 mm with a range of shell thickness of 0.340 to 0.483 mm and the average egg volume of various types of Kedu chickens was 34 ± 3.64 mm with a range of egg volumes of 25 to 39. mm. Anava test results showed that the type of chicken kedu had no significant effect on shell thickness and egg volume. Conclusion. The conclusion is that various types of Kedu Chicken have relatively the same shell thickness and egg volume.